Antioxidant Activity Test of Red Belt Leaf Extract (Piper crocatum) and Black Belt Leaf (Piper betle var nigra) Using The DPPH Method - Artika, Refi; Siregar, Rudi Munzirwan (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
Antioxidant Activity Test Of Red Belt Leaf Extract (Piper crocatum) And Black Belt Leaf (Piper betle var nigra) Using The DPPH Method. Betel leaves (Piper betle L.) are among the most important agricultural products in the world, because the need for betel leaves as a raw material for traditional medicine has increased in the last decade. Betel leaves are known to contain phenolic compounds which have the potential to act as antioxidants. This study aims to determine the antioxidant activity of extracts of red betel leaves (piper crocatum) and black betel leaves (piper betle var nigra) using the dpph (1,1-diphenyl-2-picrihydrazyl) method. The research results showed that the antioxidant activity of the ethanol extract of red betel leaves, IC50, was 45,92 μg/mL, the ethanol extract of black betel leaves obtained an IC50 value of 87,09 μg/mL, and the vitamin C comparator obtained an IC50 value of 4,11. Red betel leaf extract has higher antioxidant activity than black betel leaf extract.Keywords: betel leaf (piper betle L.), antioxidant, dpph DOI:10.23960/jppk.v13i2.30534